Produksi Hijauan dan Komposisi Botanis di Padang Penggembalaan Alam Desa Ujung Baru Kecamatan Tanasitolo Kabupaten Wajo - Sema (Jurnal Ilmu dan Industri Peternakan, 2023)
The research objective was to determine forage production and botanical composition in natural grazing in Ujung Baru Village, Tanasitolo District, Wajo Regency. This research method uses a descriptive analysis method that describes the condition of the pasture. Measurement of botanical composition using the "Actual Weight Estimate" method using a measuring quadrant of 1 m x 1 m. The data taken in this study are primary data and secondary data. Primary data were obtained from direct measurements in the field of ten samples with a land area of one ha, while secondary data was sourced from literature and related agencies. The type of primary data taken is forage production and botanical composition based on existing production data. The data obtained were tabulated and calculated to obtain the total botanical composition. The results showed that the natural pastures of Ujung Baru Village, Tanasitolo District, Wajo Regency had a dry matter production of 9.25 tonnes/ha. The average ratio of grasses, legumes and weeds is grass 33.45%, legumes 21.12% and weeds 45.43%. The conclusion that can be formulated is that the natural pasture area in Ujung Baru Village, Tanasiitolo District, Wajo Regency has decreased in production because the grazing area is dominated by weeds, namely 45.43%.